A Comparative of Physical and Digital Flash Card in Vocabulary Mastery at SMP Negeri 1 Baranti - Citra karisma; Sam Hermansyah; Buhari Buhari; Isumarni Isumarni (Universitas Muhammadiyah Enrekang, 2025)
This study compares the effectiveness of physical and digital flashcards in English vocabulary mastery at SMP Negeri 1 Baranti. The research employs a quasi-experimental method with a pre-test and post-test design to measure students' vocabulary comprehension improvement after using both types of flashcards. The sample consists of eighth-grade students divided into two groups, each using either physical or digital flashcards as learning media. The results indicate that digital flashcards are more effective in improving post-test scores compared to physical flashcards. However, based on a questionnaire given to students, most preferred physical flashcards due to their visually engaging appearance and better focus during use. On the other hand, digital flashcards provide advantages in accessibility and audio features that aid pronunciation learning. The study concludes that digital flashcards significantly enhance students' vocabulary mastery, yet student preferences still lean toward physical flashcards. The findings provide insights for educators in selecting appropriate learning media that align with students' needs and preferences to optimize English language teaching effectiveness.